Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques